THE EFFECT OF RECENCY, FREQUENCY AND MONETARY ON INVESTMENT DECISION - Sutyanto, David Nathanael (Asia Pacific Journal of Management and Education (APJME), 2022)
The dynamic behavior of individual investors provides the basis for the analysis related to recency, frequency and monetary. It aimed to find out a certain pattern in buying or selling the shares. This condition encourages to prove scientifically the phenomenon that occurred. The investment behavior data used were for 5 years to ensure the change in the investment behavior patterns. The analysis used is Kruskall Walis analysis because the data were categorized as abnormal. The results of the study showed that investor behavior can be grouped using the recency, monetary and frequency approaches